Church Management Information System of Syaloom Imandi Bolaang Mongondow - Rillya Arundaa; Yohanes Bery Mokalu; Sanriomi Sintaro (NUANSA INFORMATIKA, 2025)
GMIBM Syaloom Imandi Church is a community service organization under the GMIBM Synod headquartered in Kotamobagu. However, its information management system remains uncomputerized, leading to inefficiencies in church services, such as managing congregational data, worship schedules, church inventory, and ongoing programs. These tasks rely on physical archives and announcements during worship, posing challenges in data retrieval and increasing the risk of data loss. To address these issues, a management information system is proposed to improve the accessibility and reliability of church-related information. The management information system is developed using the Spiral Model and implemented with PHP programming and MySQL database. It provides updated information, managed by the Church Secretary, including the church's history, organizational structure, vision and mission, worship schedules, activities, congregation data, offerings, inventory records, correspondence, and church-related news. The system is web-based, ensuring easy access for users anytime and anywhere. The study resulted in a web-based church management information system that facilitates the Church Secretary in efficiently delivering essential information to the congregation, enhancing service quality and operational efficiency. This system ensures seamless communication and better management of church resources and activities.